2017
DOI: 10.5114/reum.2017.66683
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold digital capillaroscopic findings in patients with diffuse and limited cutaneous systemic sclerosis

Abstract: BackgroundSystemic sclerosis (SSc) is a chronic disease with microvascular damage. Nailfold capillaroscopy is a non-invasive method used for evaluating capillaries in SSc. Its findings could be related to the internal organ involvement and SSc course. In this study, we aimed to determine the association of the capillaroscopic patterns of nailfold capillaries with the disease subtypes of SSc, disease duration, and clinical manifestations.Material and methodsSeventy patients with SSc (15 cases with diffuse cutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The technique is widely accepted as a diagnostic tool [ [3] , [4] , [5] ], even forming part of the diagnostic criteria of SSc defined by the American College of Rheumatology and the European League Against Rheumatism [ 6 ]. However, capillaroscopy does not provide detailed images of nailfold microvasculature under certain conditions, such as when the patient's skin around the nail is thick [ 7 , 8 ]. The penetration depth of optical microscopy is limited to approximately 200 μm because tissue strongly scatters light [ 9 ], and penetration is even shallower (few tens of micrometers) for the bright-field microscopy used for capillaroscopy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technique is widely accepted as a diagnostic tool [ [3] , [4] , [5] ], even forming part of the diagnostic criteria of SSc defined by the American College of Rheumatology and the European League Against Rheumatism [ 6 ]. However, capillaroscopy does not provide detailed images of nailfold microvasculature under certain conditions, such as when the patient's skin around the nail is thick [ 7 , 8 ]. The penetration depth of optical microscopy is limited to approximately 200 μm because tissue strongly scatters light [ 9 ], and penetration is even shallower (few tens of micrometers) for the bright-field microscopy used for capillaroscopy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Capillary loss in NVC findings is observed in the late phase in SSc patients and related to the skin fibrosis progression 16,34 . In the present study, there was a significant positive correlation between the score of capillary loss and the total fibrosis score on chest HRCT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Herrick et al found that reduced capillary density was associated with positive anti-centromere antibody [26]. Another study found that anti-centromere was significantly more prevalent in early and active pattern on capillaroscopy than late scleroderma pattern [27]. Most of the other recent studies failed to find significant relationship between ACA positivity and Nailfold Capillaroscopy in Rheumatic Diseases DOI: http://dx.doi.org /10.5772/intechopen.92786 NFC parameters [13,22].…”
Section: Nailfold Capillaroscopy and Correlation With Organ Involvementmentioning
confidence: 99%